Advances and challenges in understanding histone demethylase biology. (August 2016) - Nowak, Radoslaw P; Tumber, Anthony; Johansson, Catrine; Che, Ka Hing; Brennan, Paul; Owen, Dafydd; Oppermann, Udo
Graphical abstract: Highlights: Histone methylation is critical in genome integrity and gene regulation. Histone lysine demethylation is accomplished by two distinct KDM enzyme families. Inhibitor development is ongoing including first clinical trials in oncology. Genetic and inhibitor approaches are needed to dissect the complex biology of KDMs. Cellular metabolic states control KDM activity and chromatin methylation. Abstract : Within the last decade we have witnessed significant progress in the field of chromatin methylation, ranging from the discovery that chromatin methylation is reversible, to the identification of two classes of oxidative chromatin demethylases. Multiple genetic and cellular studies emphasize the role of members of the amine oxidase and 2-oxoglutarate oxygenase enzyme families involved in methyl-lysine in physiology and disease. Advances in understanding of the underlying biochemistry have resulted in development of first series of clinical inhibitors and tool compounds which continue to resolve and help understand the complex relationships between chromatin modification, control of gene expression and metabolic states.